Analysis of Recreational Necessities and Interests of Senior Citizens from “Albergue San José Obrero” in Siquirres: Recreational Proposal - Romero Morales, Grettel (2010)
This article includes the analysis of the recreational necessities and interests of senior citizens at â€œAlbergue San José Obreroâ€ in Siquirres, and a recreational proposal that meets their requirements. The approach used in this research was an investigative- action qualitative research, thus qualitative interviews, focus group discussions, checklists and field diaries were used as measuring instruments. Information about recreational necessities and interests were obtained through an institutional analysis, information about the general condition of the elderly and the opinions from older people about their recreational experiences and preferences. The data was analyzed using the summary and systematization techniques. The study showed the necessities in this population to maintain their physical and cognitive status, their relationship with society, their sense of belonging, a sense of usefulness and self-sufficiency; plus interest to participate in crafts, outings, learning activities, physical activities, planting, fishing, storytelling, bingo and cooking activities. Based on the conclusions of the diagnosis, a recreational proposal was elaborated with the description of twelve recreational activities to be implemented in the study population. The proposed activities include: induction to recreation, cooking activities, crafts, games, walks, planting, physical and intellectual activities.